Sex differences in the regulation of porcine coronary artery tone by perivascular adipose tissue: a role of adiponectin? - Ahmad, Abdulla; Randall, Michael D.; Roberts, Richard E. (Wiley, 2017)
Background and Purpose- As there is sexual dimorphism in the regulation of vascular tone, the aim of this present study was to determine whether there are sex differences in perivascular adipose tissue (PVAT) - mediated regulation of the porcine coronary artery (PCA) tone. Experimental Approach- Isometric tension recording system was used to record changes in tone in PCAs. Western blot analysis was performed to examine the expression of adiponectin in PVAT and adiponectin receptors (adipo 1 receptor and adipo 2 receptor) and adiponectin binding protein (APPL1) in PCA. The level of adiponectin released from PVAT was measured using ELISA. Key Results- In the presence of adherent PVAT, contractions to the thromboxane mimetic U46619 and endothelin-1 were significantly reduced in PCAs from females, but not males. In PCAs pre-contracted with U46619, re-addition of PVAT caused relaxation in PCAs from females, but not males. This relaxant response in females was attenuated by combined inhibition of NO synthase (with L-NAME) and cyclooxygenase (with indomethacin). Pre-incubation with an anti-adiponectin antibody abolished the relaxant effects of PVAT. The adiponectin receptor agonist (adipoRon) produced a greater relaxation in PCAs from females compared to males. However, there was no difference in either expression or release of adiponectin from PVAT between sexes. Similarly, there was no difference in expression of adiponectin receptors or the adiponectin receptor adaptor protein APPL1 in PCAs. Conclusion and Implications- These findings demonstrate a clear sex difference in the regulation of coronary artery tone in response to adiponectin receptor stimulation, which may underlie the anticontractile effects of PVAT in females.